Strike Bulletin No.1, published by Spen and District Trades and Labour Council, 4 May 1926 (page 1) (Spen)
1926-05-04 "Strike Bulletin No.1, published by Spen and District Trades and Labour Council, 4 May 1926 (page 1)" [g0132001.jpg], 4 May 1926, Spen and District Trades and Labour Council Local Organisation